Deux modalités de la peine et leurs effets sur le criminel - Cusson, Maurice (Acta Criminologica, 1974)
AbstractTWO TYPES OF PUNISHMENTAND THEIR EFFECT ON THE CRIMINALThe examination of the immediate, spontaneous social reaction of groups towards deviants makes it possible to distinguish two very different types of punishment : corrective and stigmatizing. Corrective punishment is a measure intended to change the behaviour of a delinquent and to maintain him within the group. Stigmatizing punishment consists of attaching a dishonourable label to the delinquent and rejecting him from the group to which he belongs. When a person who is receptive to the influence of his group undergoes corrective punishment, his most probable reaction will be to conform to the expectations of his group. But if he is subjected to stigmatizing punishment, there is a possibility that he will interiorize the criminal identity attributed to him. He will then enter into conflict with the group and with others, and will tend to become integrated into a criminal group and become a recidivist criminal.A study of recidivism, conducted on the basis of concepts of correction and stigmatization, makes it possible to formulate the following two propositions : 1) an individual who is easily influenced by his group will have a greater tendency to recidivate if, over a substantial period of time, the predominant reaction to his offenses is one of stigmatization. He will have less of a tendency to recidivate if the predominant reaction to his offenses is corrective ; 2) penal measures influence recidivism, not directly, but through the agency of the immediate social reaction. The penal measures start a process of stigmatization from the outset, which has an effect on the probability of recidivism.The concepts of correction and stigmatization are also useful in the study of the evolution of penal measures. They make two other propositions possible : 3) the more complex societies become, the less the State tends to resort to stigmatizing punishment and the more it resorts to corrective punishment ; 4) imprisonment is a punishment which was developed during a period of transition during which stigmatizing punishment was losing out in favour of corrective punishment. It is a mixed measure which attempts to reach a compromise between stigmatization and correction. Because it contains elements that are incompatible, the prison will eventually fall into disuse.At the level of action, the distinction between corrective punishment makes it possible to resolve seemingly insurmountable difficulties within the framework of the present ideology of treatment. It leads to the recognition of this basic fact, that all social reaction to an act that is disapproved of is a punishment, and care must be taken to safeguard the rights of thedelinquent, even when we claim to be treating him. Furthermore, this concept leads to the admission that all punishment is liable to contain elements of stigmatization. Only measures that are strictly necessary should therefore be applied to the delinquent, for fear of releasing, in an excess of zeal, a process of stigmatization that will only accentuate the delinquent's anti-social tendencies.